La Geopolítica Del Terrorismo En Tiempos De ISIS - Mancuso, Francesco (European Scientific Journal, ESJ, 2017)
During the last years, Islamic State has expanded its military capabilities and controls a large portion of Iraq and Syria. Religious terrorism is the principal argument in international relations, but there is not a clear definition of terrorism and the countries do not find a common strategy to fight against this threat. In this article, an analysis of terrorism from a geopolitics perspective is presented with a description of the main difficulties to define this phenomenon. At the same time, there is a description of the events that allow to ISIS to expand terror and define itself as a State. This State is transforming the map of the Middle East. The Iraqi crisis contained due to fighting ISIS can lead to the division of the country into three parts: Kurdistan, Sunni Iraq, and Chita Iraq. Finally, there is an analysis of the different interests of the coalitions that fight against ISIS; the first coalition is led by Russia and the second coalition is led by the United States of America.